Exploring Athlete Care: An In-Depth Analysis of Injury Management for Disabled Athletes in North Sumatera - Malatua, Mangasi; Simatupang, Nurhayati; Manalu, Nimrot; Sinurat, Lilys (JUARA : Jurnal Olahraga, 2024)
As the landscape of sports continues to embrace diversity and inclusivity, the well-being of disabled athletes has gained prominence on the global stage. This study presents a comprehensive study aimed at shedding light on the intricate domain of injury management among disabled athletes in North Sumatera. Through a mixed-methods approach, this research offers a multifaceted exploration of the challenges and strategies inherent to athlete care in the context of disabilities. A diverse sample of disabled athletes representing various sports disciplines and regions across North Sumatera participated in this study. Quantitative data were collected through structured online surveys, capturing demographic information, injury history, training routines, and access to medical support. Complementing the quantitative phase, qualitative insights were derived from in-depth semi-structured interviews with selected athletes and focus group discussions involving coaches, sports medicine professionals, and sports organization representatives. The quantitative analysis revealed insights into the prevalence of injuries among disabled athletes, disparities in medical support, and the impact of training routines on injury rates. Qualitative findings illuminated athletes' experiences with injury prevention, treatment, rehabilitation, and the psychological effects of injuries. Coaches and sports medicine professionals provided perspectives on existing athlete care practices and identified areas for improvement. This study contributes a nuanced understanding of injury management within the realm of disabled sports in North Sumatera. As North Sumatera and the broader sporting community strive for inclusivity and excellence, this study serves as a valuable resource to guide the evolution of athlete care practices for disabled athletes.